Smart KWH monitoring and control of home appliances via internet of things (IOT) - Alghafari, Marwan Nagi Mohamed, 1993-, author 629611 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Thesis (Sarjana Kejuruteraan (Elektronik dan Telekomunikasi))